PERBEDAAN KEMAMPUAN MEMECAHKAN MASALAH ANTARA SISWA YANG MENGGUNAKAN MODEL PEMBELAJARAN PBL (Problem Based Learning) DENGAN MODEL MODIFIED FREE INQUIRY PADA KONSEP PENCEMARAN LINGKUNGAN DI KELAS X SMA NEGERI 2 KUNINGAN - edi junaedi (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2015)
The title of this research is â€œThe Difference of Solving Problem Ability Between Students Using Problem Based Learning (PBL) Model and Modified Free Inquiry Model at Environment Pollution Concept in the Tenth Class of SMAN 2 Kuninganâ€. The background of this research is the lack of students ability in solving the problem because the teacher seldom evaluated the students based on the ability of solving the problem. The other reason of this reseach is to know the better model for increasing the students ability in solving the problem. The purpose of this research is to know the difference of solving problem ability between students using PBL model and Modified Free Inquiry model at environment pollution concept in the tenth class of SMAN 2 Kuningan. The research used quasi experiment method in two experiment classes consisted of the experiment class using Modified Free Inquiry model. The research was implemented to 62 students of the tenth class in SMA N 2 Kuningan. They were devided into 31 students of experiment class using PBL model and the other 31 students of experiment class using Modified Free Inquiry model. The ability of solving the problem was measured by using essay tes consisted of solving problem sbility sums. The tes was given on pretes and postest. The average gain score of pretest and postest result on both of experiment classes showed that the PBL experiment class is 5,04 and MFI experiment class is 2,00. The hypothesis was based on gain score by using t test and showed that the value result of t account is 34,65 and t table with freedom degree of 60 is 2,66. It means that the value of t account is t table, so there is significant difference between learning PBL model and MFI model to ability of students in solving the problem at environment pollution concept in the tenth class of SMAN 2 Kuningan. The power of PBL model is pressed at the involving problem, while the MFI model is pressed at the inquiry process. Because the problem given by the teacher to the students was not hard in the class of MFI, it caused the low response of the students to the importance of the problem in MFI class is low.Â Key words : solving problem ability, problem based learning, modified free inquiryÂ